2015
DOI: 10.1080/11263504.2015.1054449
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in pyrrolizidine alkaloids inSenecio inaequidensfrom the Val Venosta (Northern Italy)

Abstract: Senecio inaequidens is a neophyte originating from South Africa that has managed to spread to Europe and colonize large areas. This plant has toxic pyrrolizidine alkaloids (PAs) which represent a health risk to humans and animals.The aim of this work was to measure the content of pyrrolizidine alkaloids of these plants in continuous intervals over the entire growing season. The plants were separated into their organs, such as sprouts, stems, leaves and inflorescences. The pyrrolizidine alkaloids were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Opuntia stricta contains glochids in the fruit, which cause the eye irritations . Likewise, Senecio inaequidens also causes adverse health impacts as it contains retrorsine, an alkaloid of pyrrolizidine group (Eller and Chizzola, 2016). IAPS like Cortaderia selloana (GISD, 2013;Mazza et al, 2014), Spartina anglica, Caesalpinia decapetala, and Rosa rugosa (Pysˇek and Richardson, 2010) cause skin cuts and injuries owing to their sharp edge and silicate crystal depositions on leaves (Mazza et al, 2014).…”
Section: Impacts Of the Iaps On Human Healthmentioning
confidence: 99%
“…Opuntia stricta contains glochids in the fruit, which cause the eye irritations . Likewise, Senecio inaequidens also causes adverse health impacts as it contains retrorsine, an alkaloid of pyrrolizidine group (Eller and Chizzola, 2016). IAPS like Cortaderia selloana (GISD, 2013;Mazza et al, 2014), Spartina anglica, Caesalpinia decapetala, and Rosa rugosa (Pysˇek and Richardson, 2010) cause skin cuts and injuries owing to their sharp edge and silicate crystal depositions on leaves (Mazza et al, 2014).…”
Section: Impacts Of the Iaps On Human Healthmentioning
confidence: 99%
“…Biotic stress results from so-called pathogen attacks by other living organisms, among these are insects and larger grazing animals, parasites, bacteria, viruses, and fungi. Whereas, abiotic stress has an environmental background and is commonly initiated by conditions or factors such as heavy UV radiation, draft, wounding, or soil contaminated with salts or heavy metals [ 39 , 161 , 162 , 163 , 164 ]. In general, plant stress damages the integrity of the plant and is often the cause of limited plant-product quality.…”
Section: Principles Of Plant Pa Biosynthesismentioning
confidence: 99%
“…Although the standard of analysis at that time may have contributed to the alkaloid value fluctuations, it is rather unlikely that this would be the only explanation of this variation. As it is known from other poisonous plants, site and environmental conditions [ 20 ], season [ 21 , 22 ] and the ontogenetic stage [ 23 , 24 ] are likely to influence the concentrations of the toxic agents as well. Already in 1956, Uotila [ 25 ] reported that marsh horsetail collected in June was more toxic to livestock than the material collected in the autumn.…”
Section: Introductionmentioning
confidence: 99%